Mahmud Rahman, Killing the water. Stories, Nueva Delhi, Penguin Books, 2010, 201 pp. - Haro Navejas, Francisco Javier (Estudios de Asia y África, 2013)
Mahmud Rahman, Killing the water. Stories, Nueva Delhi, Penguin Books, 2010, 201 pp.